High levels of Bifidobacteriaceae are associated with the pathogenesis of Parkinson’s disease - Zuo, ShuJia; Wang, HaiJing; Zhao, Qiang; Tang, Jie; Wang, Min; Zhang, Yu; Sang, Ming; Tian, Jing; Wang, Puqing (Frontiers in Integrative Neuroscience, 2023)
Background: The diagnosis of Parkinson’s disease (PD) is complex and there are no biomarkers for early identification. Many studies have reported altered gut microbiota in patients with PD compared with healthy individuals. However, results from previous studies vary across countries. Aims: We aimed to identify gut microbiota with consistent changes in PD to establish gut microbiota biomarkers that could identify patients with PD. Methods: We extracted the mean difference (MD) and 95% confidence interval (CI) of the abundance of certain microbiota families in PD from 17 16S ribosomal RNA (16S rRNA) sequencing studies that met our inclusion criteria. We determined eight consistently altered gut microbiota families. Furthermore, we validated changes in these eight gut microbiota families with quantitative gut metagenomics in another cohort. Results: Through meta-analysis, we found that there was significantly reduced abundance of Prevotellaceae, Faecalibacterium and Lachnospiraceae in patients with PD compared with healthy controls, whereas the abundance of other families including Ruminococcaceae, Christensenellaceae, Bifidobacteriaceae, Enterobacteriaceae and Verrucomicrobiaceae was increased. In the validation cohort, only Lachnospiraceae, Ruminococcaceae and Bifidobacteriaceae showed consistent changes. Conclusions: The consistently differentially altered microbiota identified by meta-analysis not only provide new biomarkers for the diagnosis of PD, but also new potential strategies for the treatment of PD and generate further speculation on the pathogenesis of PD.